Pengaruh PDRB dan Pengeluaran Pemerintah Terhadap IPM dan Kemiskinan di Kota Langsa - Puja Silvia; Asyura; Renilda; Asnidar; Puti andiny (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The purpose of this study was to determine the effect of GDP and government spending on HDI and poverty in the city Langsa. This type of research is quantitative descriptive in which the type of data used is secondary data. This research uses multiple linear regression approach. The results of this study indicate that GRDP has a positive and significant effect on HDI in the city of Langsa, government spending has a positive and insignificant effect on HDI in the city of Langsa, GRDP has a positive and significant effect on poverty levels in the city of Langsa, government spending has a positive and insignificant effect on poverty In city of Langsa, HDI has a negative and insignificant effect on poverty in the city of Langsa.